Kinematics Theory and Applications - Wittenburg, Jens (Springer Berlin Heidelberg : Imprint: Springer, 2016)
The book deals with kinematics of mechanisms. It focuses on a solid theoretical foundation and on mathematical methods applicable to the solution of problems of very diverse nature. Applications are demonstrated in a large number of fully worked-out problems.  In kinematics a wide variety of mathematical tools is applicable. In this book, wherever possible vector equations are formulated instead of lengthy scalar coordinate equations. The principle of transference is applied to problems of very diverse nature. 15 chapters of the book are devoted to spatial kinematics and three chapters to planar kinematics. In Chapt. 19 nonlinear dynamics equations of motion are formulated for general spatial mechanisms. Nearly one half of the book is dealing with position theory and the other half with motion. The book is intended for use as reference book for researchers and as textbook in advanced courses on kinematics of mechanisms.